Early Anti-Xa Assay-Guided Low Molecular Weight Heparin Chemoprophylaxis is Safe in Adult Patients with Acute Traumatic Brain Injury. Issue 4 (April 2020) - Rodier, Simon G.; Kim, Mirhee; Moore, Samantha; Frangos, Spiros G.; Tandon, Manish; Klein, Michael J.; Berry, Cherisse D.; Huang, Paul P.; Dimaggio, Charles J.; Bukur, Marko
This study evaluated the safety of early anti-factor Xa assay–guided enoxaparin dosing for chemoprophylaxis in patients with TBI. We hypothesized that assay-guided chemoprophylaxis would be comparable in the risk of intracranial hemorrhage (ICH) progression to fixed dosing. An observational analysis of adult patients with blunt traumatic brain injury (TBI) was performed at a Level I trauma center from August 2016 to September 2017. Patients in the assay-guided group were treated with an initial enoxaparin dose of 0.5 mg/kg, with peak anti-factor Xa activity measured four hours after the third dose. Prophylactic range was defined as 0.2 to 0.5 IU/mL with a dose adjustment of ± 10 mg based on the assay result. The assay-guided group was compared with historical fixed-dose controls and to a TBI cohort from the most recent Trauma Quality Improvement Project dataset. Of 179 patients included in the study, 85 were in the assay-guided group and 94 were in the fixed-dose group. Compared with the fixed-dose group, the assay-guided group had a lower Glasgow Coma Score and higher Injury Severity Score. The proportion of severe (Abbreviated Injury Score, head ≥3) TBI, ICH progression, and venous thromboembolism rates were similar between all groups. The assay-guided and fixed-dose groups had chemoprophylaxis initiated earlier than the Trauma Quality Improvement Project group. The assay-guided group had the highest percentage of low molecular weight heparin use. Early initiation of enoxaparin anti-factor Xa assay–guided venous thromboembolism chemoprophylaxis has a comparable risk of ICH progression to fixed dosing in patients with TBI. These findings should be validated prospectively in a multicenter study.